HUBUNGAN ANTARA PRAKTIK 3M DAN FAKTOR LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI WILAYAH KERJA PUSKESMAS KAYEN KABUPATEN PATI - Ulfah Rahmawati; Tri Joko; Nurjazuli Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
One of the diseases that include extraordinary events is Dengue Hemorrhagic Fever (DHF). The incidence of dengue hemorrhagic fever is strongly influenced by existing environmental conditions and eradication of mosquito breeds such as 3M practices. The purpose of this study is to analyze the relationship between physical environmental factors of the house and 3M practices at Puskesmas Kayen work area in the Pati district. The variables in this research are 3M practice (cover, drain and bury) and environmental factors (breeding place and resting place inside and outside the house). This research is an observational research with cross sectional study approach. The population in this study is the community of DHF patients recorded at puskesmas Kayen work area in the pati district and non-dengue fever with 60 respondents. Sampling using the latest data by using sampling technique is purposive sampling. The data in this research is obtained from direct interview and observation. Then, the results of data that have been collected and analyzed using chi square with 95% confidence level followed by calculate the risk / value of OR. The results of this study indicate a relationship between the resting place / resting place outside the home (p = 0.038, OR = 3,5), the practice of closing the water reservoir (p = 0.019, OR = 4,125) and the practice of draining the water reservoir (p = 0.004, and OR = 5.5). This study concludes the relationship of resting places outside the home, the practice of draining the water reservoir and the practice of closing the water reservoir with the incidence of dengue hemorrhagic fever in the work area Puskesmas kayen Pati District. Therefore, it needs to be intensified PSN 3M campaign to the community to prevent DHF incidence.